Development, validation, and feasibility of a generic yoga-based intervention for Generalized Anxiety Disorder - Pooja More; Vinod Kumar; MR Usha Rani; Mariamma Philip; Narayana Manjunatha; Shivarama Varambally; Bangalore N. Gangadhar (Elsevier, 2021)
Context: Evidence suggests that yoga effectively manages anxiety, but techniques are derived from different yoga schools. This paper describes the development, validation, and feasibility of a generic yoga-based intervention in patients with Generalized Anxiety Disorder (GAD). Methods: The first part of the study consisted of designing a generic yoga module from the traditional and contemporary yogic literature and inputs from ten experienced yoga practitioners. The content was validated using a case-vignette method from 28 yoga experts. These yoga experts rated the usefulness of the practices on a scale of 1-5 (5-extremely useful). The second part consisted of testing the feasibility of this validated generic yoga intervention in an open-label clinical trial in patients with GAD. Two weeks of ten supervised yoga sessions (SYS) were offered by a trained yoga therapist to the recruited participants and subsequently advised for home practice. A weekly booster SYS was also provided for three months after 10SYS. Results: Yoga experts (n = 28) opined that the yoga intervention would be helpful in patients with GAD with minimal modifications. All experts opined that the module was easy to teach, learn and practice. The final yoga module retained 97.7% (42 out of 43) items of the initial module. In the feasibility study, (n = 20) patients were recruited, and fifteen followed-up after one month. All patients were able to learn and practice the final yoga module within ten sessions without any significant adverse effects. The severity of anxiety reduced substantially after the ten days of SYS and this improvement was sustained for the next 4 weeks. Conclusion: The designed generic yoga intervention was validated by yoga experts and found safe and feasible in patients with GAD. Patients obtained significant symptom reductions which need to be confirmed in randomized controlled trials.